2017
DOI: 10.2196/medinform.7680
|View full text |Cite
|
Sign up to set email alerts
|

Expert Search Strategies: The Information Retrieval Practices of Healthcare Information Professionals

Abstract: BackgroundHealthcare information professionals play a key role in closing the knowledge gap between medical research and clinical practice. Their work involves meticulous searching of literature databases using complex search strategies that can consist of hundreds of keywords, operators, and ontology terms. This process is prone to error and can lead to inefficiency and bias if performed incorrectly.ObjectiveThe aim of this study was to investigate the search behavior of healthcare information professionals, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
2
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 44 publications
(26 citation statements)
references
References 22 publications
1
25
0
Order By: Relevance
“…A recent survey of health care information professionals found there is a great need for assistance in developing complex search strategies, especially if they are to be transparent and repeatable [31]. Additionally, those respondents want to increase the specificity of searches to minimize the number of non-relevant articles.…”
Section: Comparison Of the Results With Prior Workmentioning
confidence: 99%
“…A recent survey of health care information professionals found there is a great need for assistance in developing complex search strategies, especially if they are to be transparent and repeatable [31]. Additionally, those respondents want to increase the specificity of searches to minimize the number of non-relevant articles.…”
Section: Comparison Of the Results With Prior Workmentioning
confidence: 99%
“…8 2dSearch oers utility to anyone who needs to create search strategies that are comprehensive, repeatable, and transparent. This includes applications in digital libraries, healthcare, legal research, media monitoring, patent search and recruitment/sourcing [19]. In practice, many of these would entail the development of additional, specialist adapters to support custom database integration.…”
Section: Methodsmentioning
confidence: 99%
“…It is common for healthcare information professionals to want to search more than one database, particularly when undertaking a systematic literature review [19]. In practice, this requires a process of 'translation' of the search strategy to match the syntax of the target database and the search operators it supports.…”
Section: Query Executionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study on expert search strategies among healthcare information professionals [44] showed that, for a given search task, they spend an average of 60 minutes per collection or database, 3 minutes to examine the relevance of each document, and 4 hours of total search time. When written in steps, their search strategy spans over 15 lines and can reach up to 105 lines.…”
Section: Introductionmentioning
confidence: 99%